Size matters in quantitative radar monitoring of animal migration: estimating monitored volume from wingbeat frequency. Issue 5 (5th February 2019) - Schmid, Baptiste; Zaugg, Serge; Votier, Stephen C.; Chapman, Jason W.; Boos, Mathieu; Liechti, Felix
Abstract : Quantitative radar studies are an important component of studying the movements of birds. Whether a bird, at a certain distance from the radar, is detected or not depends on its size. The volume monitored by the radar is therefore different for birds of different sizes. Consequently, an accurate quantification of bird movements recorded by small‐scale radar requires an accurate determination of the monitored volume for the objects in question, although this has tended to be ignored. Here, we demonstrate the importance of sensitivity settings for echo detection on the estimated movement intensities of birds of different sizes. The amount of energy reflected from a bird and detected by the radar receiver (echo power) depends not only on the bird's size and on the distance from the radar antenna, but also on the beam shape and the bird's position within this beam. We propose a method to estimate the size of a bird based on the wingbeat frequency, retrieved from the echo‐signal, independent of the absolute echo power. The estimated bird‐size allows calculation of size‐specific monitored volumes, allowing accurate quantification of movement intensities. We further investigate the importance of applying size‐specific monitored volumes to quantify avian movements instead of using echo counts. We also highlight the importance of accounting for size‐specific monitored volume of small scale radar systems, and the necessity of reporting technical information on radar parameters. Applying this framework will increase the quality and validity of quantitative radar monitoring.